Translation and validation of an Italian version of the Body Appreciation Scale-2. (June 2021) - Casale, Silvia; Prostamo, Alfonso; Giovannetti, Sara; Fioravanti, Giulia
Highlights: The Italian BAS-2 has a one-dimensional structure. BAS-2 scores achieved full invariance across sex. Men reported significantly higher scores than women. BAS-2 scores were positively correlated with self-esteem and life satisfaction. Negative associations were found with body dissatisfaction. Abstract: Body appreciation is considered a key dimension of positive body image. Tylka and Wood-Barcalow (2015) developed the Body Appreciation Scale-2 (BAS-2), a psychometrically sound measure to assess body appreciation. The present study examines various psychometric properties (i.e. factor structure, sex-based measurement invariance, and construct validity) of an Italian translation of the BAS-2 in a community sample ( N = 601; F = 50.6 %; M age = 25.72; SD = 4.81). Exploratory factor analyses with a randomly selected split-half subsample ( n = 300; F = 50 %) supported the one-dimensional factor structure among both sexes. Confirmatory factor analyses with a second split-half subsample ( n = 301; F = 51.16 %) indicated that the one-dimensional factor structure had adequate fit after some modifications were made. BAS-2 scores achieved full invariance across sex and men reported significantly higher scores than women ( d = 0.45). Further, the Italian version of the BAS-2 had good internal consistency and was positively correlated with self-esteem and life satisfaction, whereas negative associations were found with body dissatisfaction and eating disorder symptoms. Results indicated that the Italian BAS-2 has good psychometric properties.